Primary Leiomyosarcoma of Breast in an Adolescent Girl: A Case Report and Review of the Literature. (22nd March 2012) - Rane, Swapnil Ulhas; Batra, Charu; Saikia, Uma Nahar
Abstract : Leiomyosarcoma of the breast is a rare neoplasm, primarily reported in older women. Only 44 cases have been reported in world literature and to the best of our knowledge, no case has been reported from India till date. We report a case of primary breast leiomyosarcoma in an adolescent girl who underwent a lumpectomy for rapidly increasing lump in the left breast. Here we report the histological findings and immunohistochemical profile of this entity, along with a review of existing literature.